PEMEROLEHAN KALIMAT ANAK USIA 4 TAHUN STUDI KASUS : ANNISA LAILATUL ROCHMAH - Riana Adi May Santi; Luluk Isani Kulup (Universitas PGRI Adi Buana Surabaya, 2020)
The problem discussed in this study is the variety of sentences, especially in children aged 4 years, This study aims to describe how the various sentences of children at the age of 4 years. Language is a means to communicate between one another. In children language has been formed since the child is still in the womb. Sentences are part of the language, many opinions about the variety of sentences in children, the opinions of the experts developed to follow the times. In this study the range of sentences used is the variety of sentences according to Gorys Keraf. This study aims to describe the variety of sentences in children aged 4 years, research method used is descriptive qualitative research. The data in this research is data which is tangible words, phrases, and sentences that emerged from the speech of 4 year old child, especially from Annisa Lailatul Rochmah as research object. Data were analyzed using descriptive method. After the data were collected and analyzed, there were eighty-six data from three sentences, ie, minimal versus long sentences, minor versus major, and core versus transformational sentences.